Fine zircon (ZrSiO4) powder mechanical activation, a Perturbed Angular Correlation (PAC) analysis - Gauna, Matias Roberto (2017)
By means of Perturbed Angular Correlation (PAC) analysis the resulting phases during mechano-chemical activation process on zircon (ZrSiO4) commercial fine powder (D50 ≅ 0.8 µm) were accurately identified and characterized. A high energy planetary mill was employed with 850 rpm up to 120 min. The phenomenological macroscopic confirmation of the structural change and mechanical activation consisted in an important enhancement of the sintering behavior of the treated fine zircon powders. Three different well known zircon phases were identified and quantified as a function of the milling time: a fully crystalline phase, an aperiodic phase and a distorted phase. A decrease in the first two phases was accompanied by the appearance of the third one; finally, at long term treatments, a partial dissociation was observed. Particularly the resulting zirconium oxide is a highly distorted one. The results were discussed together with those obtained using XRD, SEM and laser scattering. The XRD only showed the partial dissociation of zircon and failed in the differentiation of its nanoconfigurations observed by PAC. The milling of this hard material can be optimized through the performed characterization strategy.